PENGUKURAN BEBAN KERJA KARYAWAN DENGAN MENGGUNAKAN METODE SWAT (SUBJECTIVE WORKLOAD ASSESSMENT TECHNIQUE) DAN WORK SAMPLING DI PT. XYZ - Ainul Sabrini; Jabbar M. Rambe; Dini Wahyuni (Jurnal Teknik Industri USU, 2013)
In this era of globalization, many companies are paying special attention to efficiency, effectiveness and productivity to be able to see the use of its resources in an optimal and achievements against targets. PT XYZ has a large human resource as many as 296 employees and 290 outsourced staffs. However, in some common functions of delays in the completion of the report/assignment. So that the necessary analysis and appropriate approach to analyze the workload of employees so as to optimize the use of employee time and human resources efficiency. The methods which used to analyze the workload of PT XYZ employees by using the Subjective Workload Assessment Technique (SWAT) and the Work Sampling.The results SWAT indicate that Time Load factor (T), which predominantly affects the function of employee workload Legal, External Relations and HSSE. To assistant Manager External Relations and Customer Relation assistant Physicological Stress factor(S) is more influentiall in his work. As for the assisstant Industrial Hygiene factors Mental Effort (E) which influences his work. Each employee mental burden is on high and medium category. Based on the results of work sampling showed that most employees functionality Legal, External Relations and HSSE nonproductive activities during work hours exceeding allowance given. Only assistant Industrial Hygiene to harness the full working time for productive activities. Based on the results of the study are expected workload companies can do the division of tasks and allocation of employees better.